2015
DOI: 10.1021/jacs.5b07779
|View full text |Cite
|
Sign up to set email alerts
|

Structure Sensitivity of the Oxygen Evolution Reaction Catalyzed by Cobalt(II,III) Oxide

Abstract: Quantum chemical calculations and simulated kinetics were used to examine the structure sensitivity of the oxygen evolution reaction on several surface terminations of Co3O4. Active sites consisting of two adjacent Co(IV) cations connected by bridging oxos were identified on both the (001) and (311) surfaces. Formation of the O-O bond proceeds on these sites by nucleophilic attack of water on a bridging oxo. It was found that the relative turnover frequencies for the different sites are highly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 51 publications
5
157
2
Order By: Relevance
“…Notably, both in‐plane and out‐of‐plane orientations can be controlled by choosing the support and the deposition parameters, as observed for other electrodeposited oxide films . The activities of the various planes of Co 3 O 4 are different due to dissimilar packing densities and electronic structures . This leads to variations in reactivity, depending on the ratio of exposed surfaces, as the reactivity is dependent on the exposed surfaces as well as the potential .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, both in‐plane and out‐of‐plane orientations can be controlled by choosing the support and the deposition parameters, as observed for other electrodeposited oxide films . The activities of the various planes of Co 3 O 4 are different due to dissimilar packing densities and electronic structures . This leads to variations in reactivity, depending on the ratio of exposed surfaces, as the reactivity is dependent on the exposed surfaces as well as the potential .…”
Section: Resultsmentioning
confidence: 99%
“…[6,16] The activities of the various planeso fC o 3 O 4 are different due to dissimilar packing densitiesa nd electronic structures. [17] This leads to variations in reactivity, depending on the ratio of exposed surfaces, [18] as the reactivity is dependent on the exposed surfaces as well as the potential. [17] Though thermala nd electrochemical oxidation of electrode-positedC ol eads to the formation of Co 3 O 4 ,i td oes not lead to oxidation of the Cu interlayer,a so bserved by XRD (Figure 3).…”
Section: Morphological Investigation Through Semmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-range order of the amorphous structure provides a large fraction of surface-exposed defects that act as catalytic active sites. [138,139] The expectation of high efficiency resulting from the abundant active sites has triggered numerous studies on amorphous metal oxide catalysts. Moreover, some studies have reported that the amorphous phase has advantages in terms of mechanical and electrochemical stability as the disordered structure offers structural stability.…”
Section: Amorphous Metal Oxidesmentioning
confidence: 99%
“…On the other hand, the presence of co‐catalyst (CuO or CoO) improves the photocatalytic activity of hydrogen production, due to formation of the p‐n heterojunction that effectively separates charge carriers. It is worth mentioning that CuO and CoO played different roles during the process: while CoO is expected to catalyze the O 2 evolution reaction, CuO is expected to catalyze the H 2 evolution reaction . However, the improvement by coupling ST with CuO is considerably greater than that obtained when the material is modified with CoO, indicating that reduction reaction is the controlling step in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%